ANALYSIS OF THE ROLE OF TEACHERS AND HEADMASTER IN IMPLEMENTING CURRICULUM 2013 - Iskandar Iskandar (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2015)
The study was to describe the role of teachers and headmaster in implementing curriculum 2013. The study was a qualitative approach. Research instrument is the researchers our self. Data collecting technique were used deep-interview, participation observation, and documentation. Reseach subjects are headmaster, vice headmaster, teacher, siswa, and school committee members with snowball. Key informan is principal. Research objects are: persons, concept, place, and activities. Verification of data was done by credibility, transferability, dependability, and comfirmability criteria. The research findings that: 1) The roles of teachers in curriculum implementation are as translator, counselor, evaluator, leader; facilitator, drafter, actor, participant, and motivator; 2) headmaster has role as planning, implementation, and evaluation; 3) the head of the madrasah has a larger role than the teachers, because the headmaster as one who give influence in the implementation of the curriculum at the school, while the teachers practice in the classroom. However, the two sides could collaborate with each other, so that the implementation of the curriculum can be run well; and 4) the implementation of the curriculum in MAN 3 Jakarta can be done well, thanks to the support of students, parents, school committees, and related parties